Low-cost modified reactor to produce biochar and clamshell as alternative materials from acid mine drainage problem solving. Issue 1 (March 2020) - Wibowo, Y G; Sudibyo,; Muhammad, D; Naswir, M; Muljadi, B P
Abstract: Industrial activities and the natural oxidation of metallic sulphide-ores produce sulphate-rich waters with low pH and high heavy metals content generally termed Acid Mine Drainage (AMD). This is of great environmental concern, as some heavy metals are highly toxic. Within several possibilities, biochar and clamshell is an attractive option to treat AMD and to recover metals. This study aims to describe a simple method to utilized waste of both. Pyrolysis of waste material used to change waste to biomaterial biochar and clamshell. This research showed that biochar and clamshell are potentials material to reduce AMD impacts. This research will help and acceptable for rural areas to solve AMD problems.